2018
DOI: 10.2147/ijwh.s161672
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of anatomical urethral length on stress urinary incontinence women

Abstract: ObjectiveTo evaluate the association between the length of the female urethra and urodynamic study (UDS) parameters in patients presenting with stress urinary incontinence (SUI).Patients and methodsWe retrospectively enrolled 391 women who underwent a transobturator adjustable tape sling implantation for the management of SUI between April 2009 and March 2016. All patients underwent a physical examination and UDS. Filling cystometry data that were evaluated included the Valsalva leak point pressure, and the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
2
3
1
Order By: Relevance
“…Not only the anatomy, but also the tissue quality, appears to contribute to pelvic floor dysfunction. Despite other groups reported longer urethras to be correlated with better continence 16,17,23 , our study data do not support this findings. There are a few studies available reporting longer urethras rather being associated with incontinence 36,37 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Not only the anatomy, but also the tissue quality, appears to contribute to pelvic floor dysfunction. Despite other groups reported longer urethras to be correlated with better continence 16,17,23 , our study data do not support this findings. There are a few studies available reporting longer urethras rather being associated with incontinence 36,37 .…”
Section: Discussioncontrasting
confidence: 99%
“…Urethral funneling has been shown to be anatomically associated with shortened urethras as well as with urinary incontinence in up to 97% 17 . Other groups found a positive correlation between anatomical urethral length and urethral closure 23 . Therefore, we hypothesized shorter urethras to be associated with ISD and preoperative incontinence symptoms, and that longer post-repair urethras would be associated with better postoperative continence.…”
mentioning
confidence: 88%
“…We found that FUL shortened significantly in women with higher stages of AVWP. Our finding is similar to the results of Shin et al 20 However, only FUL at rest significantly decreased in different groups in our study. FUL during stress did not have the same result.…”
Section: Discussionsupporting
confidence: 93%
“…FUL is an important factor which may lead to SUI, urethral hypermobility, and intrinsic sphincter deficiency when urethral dysfunction transpires 20,21 . FUL in women with SUI was apparently shorter than in women without SUI 22 .…”
Section: Discussionmentioning
confidence: 94%
“…Effects of perineal anatomy characteristics on SUI is one of the hottest topic in urogynecology. Shin et al investigated the relation between urethral length and SUI, and authors claimed that patients with SUI had a significantly shorter urethral length than in patients without SUI [4]. In another study, Athanasopoulos and colleagues evaluated the correlation between perineal measurement parameters (perineal body length, fourchette-coccyx distance, anal-coccyx length) and SUI in women; however, authors found perineal measurement parameters had no effect on SUI [5].…”
Section: Introductionmentioning
confidence: 99%